2018
DOI: 10.1017/s0001972017001152
|View full text |Cite
|
Sign up to set email alerts
|

Browsers and phone girls: the intricate socialities of friendship, trust and cyberlove in Nima (Accra)

Abstract: The young men of Nima, a popular neighbourhood in Accra, organize themselves in small age groups that meet almost daily in a specific spot, to chat, play and ‘wait’, while dreaming together of a better future in a distant elsewhere. The friendships that find root in these so-called bases, which often have names such as ‘Chicago’ or ‘Brooklyn’, lead to hope and specific modes of action through which these young people engage with the city, the wider world and their own aspirations. Taking these bases as an ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…The above view of the informant is an indicator that, within the Sakawa fraternity, jargon or slang is prioritised not only for communication purposes but also for reasons of confidentiality and privacy among members. The findings here confirm what Cassiman's (2018) studies revealed in Nima, where 'hit' or 'hitting' was a widely used term to mean successful receipt of money transfers from victims, something outside persons could not normally comprehend. Similarly, Oduro-Frimpong (2011, p.2) concluded that a 'hit' mainly applies to the successful receipt of money from a money transfer service, such as Western Union, WorldRemit, Remitly, TransferWise, Money Gram and so on.…”
Section: Theme 1: Language (Slang and Jargon)supporting
confidence: 88%
See 4 more Smart Citations
“…The above view of the informant is an indicator that, within the Sakawa fraternity, jargon or slang is prioritised not only for communication purposes but also for reasons of confidentiality and privacy among members. The findings here confirm what Cassiman's (2018) studies revealed in Nima, where 'hit' or 'hitting' was a widely used term to mean successful receipt of money transfers from victims, something outside persons could not normally comprehend. Similarly, Oduro-Frimpong (2011, p.2) concluded that a 'hit' mainly applies to the successful receipt of money from a money transfer service, such as Western Union, WorldRemit, Remitly, TransferWise, Money Gram and so on.…”
Section: Theme 1: Language (Slang and Jargon)supporting
confidence: 88%
“…Therefore, female scammers with names such as Hawa, Salma, Ni'mah and Zainab in orthodox Muslim Zongo communities as revealed in Cassiman study in Nima and Accra, transgress the moral standard of womanhood and may find it difficult in settling down in marriage (Cassiman, 2019, p. 494). Cassiman's (2018Cassiman's ( , 2019 conclusions are worth noting. Her studies confirm that the readiness of Sakawa boys to cede their roles in online dating scams to girls to ingeniously execute a grand scheme in cybercrime challenges gender relations and norms.…”
Section: Gender Fraud Through Online Dating and Relationshipmentioning
confidence: 96%
See 3 more Smart Citations